Treatment of brucellosis in a young child with trimethoprim/sulfamethoxazole anaphylaxis - Demet Teker; Gonul Tanir; Serap Ozmen; Turkan Aydın Teke; Sennur Keles; Ilknur Bostancı (Elsevier, 2014)
Summary: Brucellosis is a common zoonotic disease throughout the world. Brucella spp. transmit to humans through contact with fluids of infected animals, especially sheep, cattle, and goats. It is also transmitted by ingestion of fluid-derived products of infected animals, such as unpasteurized milk and cheese. Brucella spp. changes pH level of intracellular environment, so the first treatment approach is to administer antibiotics that have activity in acidic conditions. Anti-brucellosis treatment regimens include doxycycline for children older than eight years old and rifampicin and trimethoprim/sulfamethoxazole (TMP-SMX) combination therapy for children under eight years old, which may be able to act intracellularly under acidic conditions. A TMP-SMX allergy causing anaphylaxis has been reported previously. No alternative anti-brucellosis treatments have been reported in the literature for patients under eight years old with a TMP-SMX allergy. Here, we report a case of a child with brucellosis and a TMP-SMX allergy who was under eight years old at the time of diagnosis and was successfully treated with rifampicin, ciprofloxacin, and gentamicin. Keywords: Brucellosis, Children, Trimethoprim/sulfamethoxazole, Anaphylaxis